Accelerated GWT: Building Enterprise Google Web Toolkit Applications - Gupta, Vipul (Apress, 2012)
This book would not have been possible without the help of a large number of people, so I would like to sincerely thank everyone involved. Thanks in particular to the team at Apress, especially Tracy Brown Collins and Clay Andres, for helping me keep the book on track and taking care of all the details that go into getting a book printed and on the shelves. I would also like to thank Jason Gilmore for his support during the initial part of the book and Kim Wimpsett for finding and correcting the many mistakes I made during the writing process. I would also like to thank Ellie Fountain and Tina Nielsen for their help in the production and administrative processes during the writing of this book.